2005
DOI: 10.1590/s0066-782x2005000500005
|View full text |Cite
|
Sign up to set email alerts
|

Potenciação pós-extra-sistólica na cardiopatia chagásica crônica: estudo com ventriculografia de contraste radiológico

Abstract: The phenomenon of post-extrasystolic potentiation is observed in a significant proportion of patients with chronic Chagas' heart disease, in whom the phenomenon could be angiographically analyzed, indicating the existence of potentially recruitable contractile reserve in ventricular regions, showing marked dyssynergy. Additional studies for clarifying the underlying mechanisms are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Only one study directly addressed the question of hibernating myocardium in CCC. The study was performed using post-extrasystolic potentiation, which is commonly observed during radiologicalcontrast left ventriculography, and showed that most myocardial areas with impaired wall motion indeed had a contractile reserve; that is, these areas were viable 59 . However, the hypothesis that hypokinetic areas of viable myocardium, unmasked through post-extrasystolic potentiation, would be predominant in regions exhibiting scintigraphic, reversible (ischemic) perfusion defects, was not confi rmed by the results of the study 60 .…”
Section: Pathophysiological Consequences Of Coronary Microvascular Pementioning
confidence: 99%
“…Only one study directly addressed the question of hibernating myocardium in CCC. The study was performed using post-extrasystolic potentiation, which is commonly observed during radiologicalcontrast left ventriculography, and showed that most myocardial areas with impaired wall motion indeed had a contractile reserve; that is, these areas were viable 59 . However, the hypothesis that hypokinetic areas of viable myocardium, unmasked through post-extrasystolic potentiation, would be predominant in regions exhibiting scintigraphic, reversible (ischemic) perfusion defects, was not confi rmed by the results of the study 60 .…”
Section: Pathophysiological Consequences Of Coronary Microvascular Pementioning
confidence: 99%
“…The contrast ventriculography was then analysed according to a 9-segment model using a quantitation score that ascribed 1 to normal wall motion, 2 to hypokinesis, 3 to akinesia and 4 to dyskinesis. 20 An index of the global wall motion was obtained by summing the segmental scores divided by the number of segments analysed. 21 The ventriculogram also allowed the qualitative assessment of LV hypertrophy and dilation.…”
Section: Methodsmentioning
confidence: 99%
“…A ventriculografia de contraste foi então analisada de acordo com um modelo de 9 segmentos, utilizando um escore de quantificação que atribuiu 1 à mobilidade normal da parede, 2 à hipocinesia, 3 à acinesia e 4 à discinesia. 20 Um escore médio de movimentação segmentar da parede ventricular foi obtido pela soma das pontuações de cada segmento, dividida pelo número de segmentos analisados 21 conforme publicação recente de nossa instituição. O ventriculograma de contraste radiológico também permitiu a avaliação qualitativa de hipertrofia e dilatação do ventrículo esquerdo.…”
Section: Métodosunclassified
“…That study, which used the postextrasystolic potentiation technique during radiologic-contrast cineventriculography, demonstrated that it was possible to identify contractile reserve in many dyssynergic areas; therefore, it is still a viable reserve. 40,41 However, the hypothesis was not supported; the viability hidden by dyssynergia and shown through postextrasystolic potentiation could predominate or only appear in regions showing reversible perfusion defects during myocardial scintigraphy. 42 The second and perhaps most decisive mechanism would result in cellular death and consequent repairing fibrosis.…”
Section: Physiopathological Consequences and Opportunities For Therapmentioning
confidence: 99%